SCJP: Sun Certified Programmer for Java® Platform, SE6, Study Guide - Raposa, Richard F (Sybex, 2009)
Sun's foundation-level Sun Certified Java Programmer (SCJP) for Standard Edition 6 is a must-have for any Java programmer, and is a prerequisite for Sun's specialty certifications. This resource is essential preparation for the SCJP and focuses heavily on the skill set that Sun expects its SCJPs to have, with numerous examples, exercises, and real-world scenarios to give readers the tools needed to use what they learn. The material covers declarations, initialization, and scoping; flow control; API contents; concurrency; object-oriented concepts; collections/generics; and fundamentals. The interactive CD-ROM features chapter review questions, two bonus exams, a series of flashcards that can be used on PCs or handheld devices, and an e-book.Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.